2018
DOI: 10.1002/pip.3042
|View full text |Cite
|
Sign up to set email alerts
|

Measuring carrier injection from amorphous silicon into crystalline silicon using photoluminescence

Abstract: In devices with intrinsic amorphous silicon layer on a crystalline silicon substrate, the light absorbed in the amorphous layer can be weakly electronically coupled into the silicon base. Such carrier injection has previously been reported from measurements on finished devices containing stacks of intrinsic and doped amorphous silicon layers. Here, we use spectral response of photoluminescence, a contactless approach, to investigate this carrier injection on significantly simpler structures. In such devices, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 24 publications
(48 reference statements)
0
12
1
Order By: Relevance
“…The thickness of the ITO layers and the front a‐Si:H layer were set to 80 and 6 nm, respectively. The latter was chosen to be smaller than the actual thickness in the fabricated cells (~10 nm as a sum of p ‐layers and i ‐layers), by taking the partial charge‐carrier collection within the a‐Si:H layer into consideration . For simplicity, the AR film used in Figure C was not applied here.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thickness of the ITO layers and the front a‐Si:H layer were set to 80 and 6 nm, respectively. The latter was chosen to be smaller than the actual thickness in the fabricated cells (~10 nm as a sum of p ‐layers and i ‐layers), by taking the partial charge‐carrier collection within the a‐Si:H layer into consideration . For simplicity, the AR film used in Figure C was not applied here.…”
Section: Resultsmentioning
confidence: 99%
“…23 In the simulation, we ation. 36,37 For simplicity, the AR film used in Figure 4C was not applied here. Under these assumptions, we simulated the spectral absorptance within the Si wafer, which is equivalent to EQE when assuming perfect carrier collection.…”
Section: Current Density and Optical Lossesmentioning
confidence: 99%
“…Holman et al state a J SC loss of 2 mA/cm 2 in the wavelength range between 300 nm and 800 nm due to parasitic absorption at the front-side for a typical SHJ solar cell [53] with ITO as TCO. While charge carriers generated in the doped a-Si:H can be considered as fully lost due to the short diffusion length in the material, it is reported that at least parts of the carriers generated in the a-Si:H(i) layer are injected in the c-Si absorber and thus contribute to J SC [53,54] Holman et al estimate that 30% of the carriers contribute to J SC [53], while Paduthol et al report even 40% [54].…”
Section: Loss Mechanisms and Mitigation Strategiesmentioning
confidence: 99%
“…Thus, the IQE with carrier injection efficiency β (IQE β ) can be defined as IQEβ(λ)=(ASi(λ)+β×Apoly(λ))/(1R(λ)), where ASi is the absorption in the Si absorber layer, Apoly is the absorption in poly‐Si layer, R is the external front reflectance of the finished cell, and λ is the wavelength of incident light. [ 23 ] Note that IQE β = 0 refers to a collection efficiency of 1 for all absorbed photons in the c‐Si base without recombination losses. It is thus to be taken as the maximum possible IQE under the assumption that only photons absorbed in the c‐Si base contribute to the photocurrent of the solar cell.…”
Section: Utilization Of Charge Carriers Generated In the Poly‐simentioning
confidence: 99%
“…It has previously been shown in literature for silicon heterojunction solar cells that carriers that are photo‐generated in the amorphous silicon can be efficiently electronically injected into the crystalline silicon, adding to the cell's photocurrent. [ 23–25 ] Here we analyze this effect and vary the poly‐Si thickness on the front, including ultra‐thin (down to 10 nm) values for the cells with POLO junctions. This effect would reduce the parasitic absorption in the poly‐Si as compared with the expectations based on ray‐tracing simulations.…”
Section: Introductionmentioning
confidence: 99%